Fixed-point theorems for integral-type contractions on partial metric spaces - Altun, I.; Masiha, H. P.; Sabetghadam, F. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We present some fixed-point results for single-valued mappings on partial metric spaces satisfying a contractive conditionof integral type.